Do the information platforms of the branches of governments of Brazilian states contribute to build passive transparency? - Drehmer, Amanda Finck; Raupp, Fabiano Maury (Revista de Administração da UFSM, 2020)
The objective of the article was to investigate the contributions of the information platforms of the branches of governments of Brazilian states to build passive transparency. A descriptive study was carried out, through documentary research, with a predominantly qualitative approach. The object of investigation comprises the executive, legislative and judicial branches of governments of Brazilian states. The data were collected in February 2017 using the structured observation technique, through a protocol for recording information. The data obtained were analyzed using the descriptive analysis technique. The indicators for evaluation of the platforms were ‘communication’, ‘login and receipts’ and ‘barriers’, and they presented different configurations in each of the branches. In terms of ‘communication’ and ‘login and receipts’, in general, the state executive branch received better scores compared to the judiciary and legislative branches. On the other hand, the indicator ‘barriers’, was better evaluated in the judiciary and legislative branches. From the results obtained, it is not yet possible to confirm whether the platforms of the executive, judicial and legislative branches of the Brazilian states contribute to build passive transparency.